Pengaruh Kompensasi dan Jaminan Hari Tua terhadap Motivasi Kerja Pegawai di LSP Pariwisata Komodo - Kadek Wira Adi Saputra; Pande Putu Juniarta (Yayasan Literasi Sains Indonesia, 2024)
Compensation is the reward employees receive for payments made to the company, either in cash or in kind. Old age security or JHT is a benefit provided when a worker enters retirement, dies, experiences permanent disability or leaves Indonesia without plans to return. Work motivation is the driving force or motivation of each employee in carrying out their duties. This motivation is an important aspect because if employees are not given sufficient motivation then their duties will not be carried out optimally. Based on the problem formulation given. This research was conducted at the Komodo Tourism LSP, which is a professional certification institution under BNSP which has the task of certifying workers, especially in the tourism sector. The aim of this research is to analyze the influence of rewards on the work motivation of LSP Pariwista Komodo employees, to analyze the influence of old age security on the work motivation of LSP Pariwista Komodo employees. This research was conducted at LSP Pariwista Komodo by giving a questionnaire of 30 questions to 30 people chosen randomly from 12 employees. The T-table value obtained after data processing was 2.051. Therefore, the research results show that there is a positive and significant influence between salary on employee work motivation with a T test value of 7.943. and has a positive and significant effect on the safety of the elderly and employee work motivation with a T test value of 6.024. Rewards and old age security together have a significant influence on employee work motivation at 69%.